The effects of simultaneous isometric and eccentric- or concentric-biased exercise on cardiovascular and muscular health of young individuals - A. W. Baross; B. H. Wright; D. A. Langdon; A. D. Kay; M. Cauchi; A. Clarke; B. Pitham; C. Willmont; T. Barnett; C. Key; M. Reynolds; A. Thomas; et al. (European Journal of Applied Physiology, 2026)

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Siderophore production and utilization by marine bacteria in the North Pacific Ocean - Jiwoon Park; Bryndan P. Durham; Rebecca S. Key; Ryan D. Groussman; Zinka Bartolek; Paulina Pinedo‐Gonzalez; Nicholas J. Hawco; Seth G. John; Michael C. G. Carlson; Debbie Lindell; Lauren W. Juranek; Sara Ferrón; et al. (Limnology and Oceanography, 2023)
Siderophores are strong iron‐binding molecules produced and utilized by microbes to acquire the limiting nutrient iron (Fe) from their surroundings. Despite their importance as a component of the iron‐binding ligand pool in seawater, data on the distribution of siderophores and the microbes that use them are limited. Here, we measured the concentrations and types of dissolved siderophores during two cruises in April 2016 and June 2017 that transited from the iron‐replete, low‐macronutrient North Pacific Subtropical Gyre through the North Pacific Transition Zone (NPTZ) to the iron‐deplete, high‐macronutrient North Pacific Subarctic Frontal Zone (SAFZ). Surface siderophore concentrations in 2017 were higher in the NPTZ (4.0–13.9 pM) than the SAFZ (1.2–5.1 pM), which may be partly attributed to stimulated siderophore production by environmental factors such as dust‐derived iron concentrations (up to 0.51 nM). Multiple types of siderophores were identified on both cruises, including ferrioxamines, amphibactins, and iron‐free forms of photoreactive siderophores, which suggest active production and use of diverse siderophores across latitude and depth. Siderophore biosynthesis and uptake genes and transcripts were widespread across latitude, and higher abundances of these genes and transcripts at higher latitudes may reflect active siderophore‐mediated iron uptake by the local bacterial community across the North Pacific. The variability in the taxonomic composition of bacterial communities that transcribe putative ferrioxamine, amphibactin, and salmochelin transporter genes at different latitudes further suggests that the microbial groups involved in active siderophore production and usage change depending on local conditions.

Clustering of KOR PET images separates people with AUD into distinct responses to naltrexone - Jocelyn Hoye; Jose Key; Bart de Laat; Kelly P. Cosgrove; Suchitra Krishnan-Sarin; Xenophon Papademetris; Evan D. Morris (Brain Imaging and Behavior, 2023)

Glycine betaine uptake and metabolism in marine microbial communities - Angela K. Boysen; Bryndan P. Durham; William Kumler; Rebecca S. Key; Katherine R. Heal; Laura T. Carlson; Ryan D. Groussman; E. Virginia Armbrust; Anitra E. Ingalls (Environmental Microbiology, 2022)
Summary Glycine betaine (GBT) is a compatible solute in high concentrations in marine microorganisms. As a component of labile organic matter, GBT has complex biochemical potential as a substrate for microbial use that is unconstrained in the environment. Here we determine the uptake kinetics and metabolic fate of GBT in two natural microbial communities in the North Pacific characterized by different nitrate concentrations. Dissolved GBT had maximum uptake rates of 0.36 and 0.56 nM h −1 with half‐saturation constants of 79 and 11 nM in the high nitrate and low nitrate stations respectively. During multiday incubations, most GBT taken into cells was retained as a compatible solute. Stable isotopes derived from the added GBT were also observed in other metabolites, including choline, carnitine and sarcosine, suggesting that GBT was used for biosynthesis and for catabolism to pyruvate and ammonium. Where nitrate was scarce, GBT was primarily metabolized via demethylation to glycine. Gene transcript data were consistent with SAR11 using GBT as a source of methyl groups to fuel the methionine cycle. Where nitrate concentrations were higher, more GBT was partitioned for lipid biosynthesis by both bacteria and eukaryotic phytoplankton. Our data highlight unexpected metabolic pathways and potential routes of microbial metabolite exchange.

At-sea distribution and foraging tactics in a monomorphic tropical seabird - D. Z. Keys; F. Orgeret; M. Le Corre; A. Jaeger; P. A. Pistorius (Marine Biology, 2021)

An Exploratory Study of Occupational Safety and Health with Limited Resource African-American Farmers - Corey D. Key; John R. Wheat (Journal of Agromedicine, 2021)

OpenMendel: a cooperative programming project for statistical genetics - Hua Zhou; Janet S. Sinsheimer; Douglas M. Bates; Benjamin B. Chu; Christopher A. German; Sarah S. Ji; Kevin L. Keys; Juhyun Kim; Seyoon Ko; Gordon D. Mosher; Jeanette C. Papp; Eric M. Sobel; et al. (Human Genetics, 2020)

Dietary greenhouse gas emissions of meat-eaters, fish-eaters, vegetarians and vegans in the UK - Peter Scarborough; Paul N. Appleby; Anja Mizdrak; Adam D. M. Briggs; Ruth C. Travis; Kathryn E. Bradbury; Timothy J. Key (Climatic Change, 2014)

Interactive Effects of Mosquito Control Insecticide Toxicity, Hypoxia, and Increased Carbon Dioxide on Larval and Juvenile Eastern Oysters and Hard Clams - R. N. Garcia; K. W. Chung; P. B. Key; L. E. Burnett; L. D. Coen; M. E. DeLorenzo (Archives of Environmental Contamination and Toxicology, 2014)

Physical activity, sex steroid, and growth factor concentrations in pre- and post-menopausal women: a cross-sectional study within the EPIC cohort - S. Rinaldi; R. Kaaks; C. M. Friedenreich; T. J. Key; R. Travis; C. Biessy; N. Slimani; K. Overvad; J. N. Østergaard; A. Tjønneland; A. Olsen; S. Mesrine; et al. (Cancer Causes & Control, 2014)

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Mineral system analysis of the Mt Isa–McArthur River region, Northern Australia - F. C. Murphy; L. J. Hutton; J. L. Walshe; J. S. Cleverley; M. A. Kendrick; J. Mclellan; M. J. Rubenach; N.H. S. Oliver; K. Gessner; F. P. Bierlein; B. Jupp; L. Aillères; et al. (Australian Journal of Earth Sciences, 2011)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Recent range expansions in non-native predatory beetles on sub-Antarctic South Georgia - P. Convey; R. S. Key; R. J. D. Key; M. Belchier; C. L. Waller (Polar Biology, 2011)

Partitioning of major and trace inorganic contaminants in fly ash acid mine drainage derived solid residues - W. M. Gitari; L. F. Petrik; D. L. Key; C. Okujeni (International Journal of Environmental Science and Technology, 2010)

Fruits and vegetables consumption and the risk of histological subtypes of lung cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) - F. L. Büchner; H. B. Bueno-de-Mesquita; J. Linseisen; H. C. Boshuizen; L. A. L. M. Kiemeney; M. M. Ros; K. Overvad; L. Hansen; A. Tjonneland; O. Raaschou-Nielsen; F. Clavel-Chapelon; M.-C. Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Combination therapies that inhibit cyclooxygenase-2 and leukotriene synthesis prevent disease in murine collagen induced arthritis - G. D. Anderson; K. L. Keys; P. A. De Ciechi; J. L. Masferrer (Inflammation Research, 2009)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Direct inoculation of RNA transcripts from an infectious cDNA clone of porcine reproductive and respiratory syndrome virus (PRRSV) into the lymph nodes and tonsils of pigs initiates PRRSV infection in vivo - K. F. Key; J. DiCristina; J. Gillespie; D. K. Guenette; X. J. Meng (Archives of Virology, 2007)

Chemical and physical speciation of mercury in Offatts Bayou: A seasonally anoxic bayou in Galveston Bay - Seunghee Han; Ronald D. Lehman; Key-Young Choe; Gary A. Gill (Limnology and Oceanography, 2007)
A chemical equilibrium model was used to predict the solution speciation of dissolved mercury (Hg) in the stratified water column of Offatts Bayou, a subestuary in Galveston Bay, Texas, which undergoes seasonal anoxia in bottom waters. Chemical equilibrium modeling was conducted using conditional stability constants and concentrations of Hg‐complexing organic ligands experimentally determined by competitive ligand equilibration methods. Dissolved Hg complexation was dominated by interactions with sulfide and dissolved organic matter (DOM) (HOHgHS 0 , HOHgHS(DOM), HgSHS − , and HgS 2 2‐ at all depths. Sulfide and glutathione competed for methylmercury (MeHg) complexation in oxic layers; in anoxic waters, sulfide complexation dominated MeHg speciation. The particle‐water distribution coefficient (K d ) of Hg decreased in the anoxic layer of the water column, where the dissolved sulfide concentration increased, providing evidence that sulfide complexation influences the solubility of Hg. The solubility of MeHg was elevated in the anoxic as compared to the oxic layers, and this distributional feature was coincident with a change in the solution speciation of dissolved MeHg from glutathione/sulfide complexation in the oxic layers to a predominantly sulfide complexation in the anoxic layers. Maximum enrichment of Hg, MeHg, and iron (Fe) in suspended particulate matter was observed in the lower layer of the pycnocline, most likely resulting from formation of insoluble Fe oxide, which scavenged dissolved Hg‐sulfide and MeHg‐sulfide species. The concomitant decrease in dissolved inorganic Hg, Fe, and sulfide in the anoxic layers is suggested to result from scavenging of inorganic Hg by FeS, which is in accordance with the Hg speciation model. Overall, Hg cycling in the water column of Offatts Bayou was associated with sulfide and DOM complexation, Fe dissolution/precipitation, water column production of MeHg, and/or efflux of MeHg from anoxic sediment.

An evaluation of contaminated estuarine sites using sediment quality guidelines and ecological assessment methodologies - M. Fulton; P. Key; E. Wirth; A. K. Leight; J. Daugomah; D. Bearden; S. Sivertsen; G. Scott (Ecotoxicology, 2006)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

The effects of peroxovanadate and peroxovanadyl on glucose metabolism in vivo and identification of signal transduction proteins involved in the mechanism of action in isolated soleus muscle - Ricado Key Yamazaki; Sandro M. Hirabara; Osvaldo Tchaikovski; Maria Cecília Pascoal Lopes; Claudia Nogata; Júlia Aikawa; Everson A. Nunes; Ricardo A. Tanhoffer; Maurício D. Lissa; L. C. Fernandes (Molecular and Cellular Biochemistry, 2005)

Surface Water Pesticide Movement from the Dade County Agricultural Area to the Everglades and Florida Bay via the C-111 Canal - M. H. Fulton; G. I. Scott; M. E. DeLorenzo; P. B. Key; D. W. Bearden; E. D. Strozier; C. J. Madden (Bulletin of Environmental Contamination and Toxicology, 2004)

Sediment‐water exchange of total mercury and monomethyl mercury in the San Francisco Bay‐Delta - Key‐Young Choe; Gary A. Gill; Ronald D. Lehman; Seunghee Han; Wesley A. Heim; Kenneth H. Coale (Limnology and Oceanography, 2004)
Five field trips were conducted in the San Francisco Bay‐Delta between May 2000 and October 2001 to investigate the sediment‐water exchange of total mercury (Hg) and monomethyl mercury (MMHg). Solid‐phase Hg averaged ~1 nmol g −1 and did not show any variability with depth or time or among sites. In contrast, solid‐phase MMHg showed considerable vertical, temporal, and spatial variability (0.4–66 pmol g −1 ), with the highest values occurring at a peat‐rich environment in May 2001, suggesting that MMHg production was largely controlled by temporal factors and habitat type. In pore water, both Hg and MMHg concentrations were generally elevated near the sediment‐water interface during warm months. Sediment‐water exchange flux of MMHg, determined with benthic chamber deployments, ranged from −92 to 850 pmol m −2 d −1 , with higher values occurring in May. In most cases, diffusional fluxes of Hg and MMHg, estimated with the use of interfacial concentration gradients, constituted only a minor portion of the measured fluxes, suggesting the importance of advective processes on sediment‐water exchange. Surface‐water transect and time series studies conducted in Franks Tract support the commonly held belief that wetland and marsh regions are major sources for MMHg within the Delta. The integrated sediment‐water fluxes of Hg and MMHg in the study area were estimated to be 130 and 6 mmol d −1 , respectively, and the benthic input was as important a source of Hg and MMHg as the riverine input within the Delta during low‐flow months.

Dynamical and microphysical characteristics of Arctic clouds using integrated observations collected over SHEBA during the April 1998 FIRE.ACE flights of the Canadian Convair - I. Gultepe; G. A. Isaac; J. Key; J. Intrieri; D. O?C. Starr; K. B. Strawbridge (Meteorology and Atmospheric Physics, 2004)

Toxicity of the Insecticides Fipronil and Endosulfan to Selected Life Stages of the Grass Shrimp ( Palaemonetes pugio ) - P. B. Key; K. W. Chung; A. D. Opatkiewicz; E. F. Wirth; M. H. Fulton (Bulletin of Environmental Contamination and Toxicology, 2003)

Developing a Spatial Framework of Common Ecological Regions for the Conterminous United States - GERARD McMAHON; STEVEN M. GREGONIS; SHARON W. WALTMAN; JAMES M. OMERNIK; THOR D. THORSON; JERRY A. FREEOUF; ANDREW H. RORICK; JAMES E. KEYS (Environmental Management, 2001)

Tephra, snow and water: complex sedimentary responses at an active snow-capped stratovolcano, Ruapehu, New Zealand - V. Manville; K. A. Hodgson; B. F. Houghton; J. R. (H.) Keys; J. D. L. White (Bulletin of Volcanology, 2000)

Phylogenetic evaluation of 5S ribosomal RNA gene and spacer in theCallistachys group (Fabaceae:Mirbelieae) - M. D. Crisp; R. Appels; F. M. Smith; W. M. S. Keys (Plant Systematics and Evolution, 1999)

Increasing incidence of colon and rectal cancer among Hispanics and American Indians in New Mexico (United States), 1969-94 - Ann Chao; Frank D. Gilliland; William C. Hunt; Marc Bulterys; Thomas M. Becker; Charles R. Key (Cancer Causes & Control, 1998)

Ciliary neurotrophic factor blocks rod photoreceptor differentiation from postmitotic precursor cells in vitro - Matthias Kirsch; Steffen Schulz-Key; Annette Wiese; Sabine Fuhrmann; H.-D. Hofmann (Cell and Tissue Research, 1998)